2021
DOI: 10.3390/ani11061503
|View full text |Cite
|
Sign up to set email alerts
|

High Stocking Density and Food Deprivation Increase Brain Monoaminergic Activity in Gilthead Sea Bream (Sparus aurata)

Abstract: In teleosts, brain monoamines (dopamine and serotonin) participate in the early response to different acute stressors. However, little is known regarding their role during chronic stress. In a 2 × 2 factorial design, the influence of a high stocking density (HSD) and/or food deprivation (FD) on the brain monoaminergic activity in gilthead sea bream (Sparus aurata) was evaluated. Following a 21-day experimental design, samples from the plasma and brain regions (telencephalon, hypothalamus, and optic tectum) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Furthermore, based on the results of this and a previous study ( Staven et al, 2021 ), the social factor was likely the most important. Social factors were considered the most relevant because stress related alterations in the brain monoaminergic systems are usually more prominent in the serotonergic than in the dopaminergic system, both in situations of acute and prolonged stress ( Øverli et al, 2001 ; Gesto et al, 2013 ; Conde-Sieira et al, 2018 ; López-Patiño et al, 2021 ), and no alterations were found in the serotonergic system in this study. Furthermore, our previous study ( Staven et al, 2021 ) showed that both Live and Olfaction treatment were equally able to acutely modify the swimming activity of the lumpfish (in a kind of “startling” response), while only the Live treatment significantly affected the lumpfish brain in the current study.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, based on the results of this and a previous study ( Staven et al, 2021 ), the social factor was likely the most important. Social factors were considered the most relevant because stress related alterations in the brain monoaminergic systems are usually more prominent in the serotonergic than in the dopaminergic system, both in situations of acute and prolonged stress ( Øverli et al, 2001 ; Gesto et al, 2013 ; Conde-Sieira et al, 2018 ; López-Patiño et al, 2021 ), and no alterations were found in the serotonergic system in this study. Furthermore, our previous study ( Staven et al, 2021 ) showed that both Live and Olfaction treatment were equally able to acutely modify the swimming activity of the lumpfish (in a kind of “startling” response), while only the Live treatment significantly affected the lumpfish brain in the current study.…”
Section: Discussionmentioning
confidence: 95%
“…ACTH enters the bloodstream and stimulates the synthesis and secretion of glucocorticoids in the steroidogenic cells of the interrenal gland (Spiess et al, 1981; Lederis et al, 1994; Bernier, 2006; Cerdá-Reverter et al, 2011; Gesto et al, 2013). Generally, elevated blood cortisol concentrations are observed among fish in a high-density environment, which is an extremely stressful condition (Liu et al, 2017; Long et al, 2019; López-Patiño et al, 2021). However, the results of this study revealed that the expression of pro-opiomelanocortin ( pomc ), the precursor of acth , decreased in the brains of highly stocked fish, and the transcription level of crh did not show a significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, data obtained on circulating cortisol levels revealed that either of the two experimental groups was not in a stressful situation judging by their low concentrations compared to several experimental models focused on the substitution or supplementation of different ingredients in aquaculture feeds, or even related to the basal levels considered normal recorded in other species including European sea bass (Montero et al 2015;Gorissen and Flik 2016;Schreck and Tort 2016;Samaras et al 2018;López-Patiño et al 2021). Although cortisol levels were low in both treatments, the slightly significant increase observed in control fish could be related to lower antioxidant capacity compared to fish fed the GP diet.…”
Section: Changes In Fillet Quality During Storagementioning
confidence: 96%